SENSE OF PLACE KOTA BOGOR BERDASARKAN PERSEPSI PENDUDUK DI TIGA TIPOLOGI PERMUKIMAN (Sense of Place of Bogor city based on Community Perception in three typologies of Settlements) - Tohjiwa, Agus Dharma (Unika Soegijapranata Semarang, 2015)
Bogor city has three typologies of settlements that are historical area, internal development area and commuting area. The purpose of this study is to describe the sense of place in the city of Bogor based on the perception of the resident living in those settlements. This research uses a survey method using questionnaire and field observations. Research variables using three components of sense of place which are physical attributes, activities, and conception. The result shows that the natural conditions and colonial heritage still has a major contribution in creating Bogorâs sense of place. Activity as a commuter from Bogor to Jakarta is the main activity characteristics in this city. Nevertheless, at the weekend most people spend time in their own city. Most resident has a conception that Bogor is a city of tourism and resort. This study shows that Bogor urban identity as historic city only supported by a physical artifact of the empire and colonial periods alone. Activities and perceptions of people living in Bogor unrelated or unsupport the formation of urban identity. To keep the sense of place of Bogor, at least there are two aspects which should be considered which are revitalizing the old city and the development of Transit Oriented Development.